2019
DOI: 10.1097/bpo.0000000000001426
|View full text |Cite
|
Sign up to set email alerts
|

The Passive Mechanical Properties of Muscles and Tendons in Children Affected by Osgood-Schlatter Disease

Abstract: Background: Osgood-Schlatter disease (OSD) is a sports-related disorder involving apophysitis, which affects the tibial tuberosity. The identification of factors related to OSD is important for its prevention and early recovery from the disease. This study aimed to compare the passive mechanical properties of the muscle-tendon unit in children affected by an OSD and healthy children, by using ultrasound real-time tissue elastography. Methods: Eighteen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Of the 40 studies included, 25 studies reported on OSD‐related imaging findings 4‐7,9,11‐30 . Most studies used radiography (n = 10) or US (n = 6), with the remaining studies using radiography and US (n = 4), radiography and MRI (n = 3), MRI only (n = 1) and one study using both CT, MRI, radiography, and bone scintigraphy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 40 studies included, 25 studies reported on OSD‐related imaging findings 4‐7,9,11‐30 . Most studies used radiography (n = 10) or US (n = 6), with the remaining studies using radiography and US (n = 4), radiography and MRI (n = 3), MRI only (n = 1) and one study using both CT, MRI, radiography, and bone scintigraphy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight cross‐sectional 4,15,20,24,27‐30 and two case‐control studies 6,7 reported on OSD imaging findings compared to controls. In the studies that included a control group, the imaging findings described above (Table 1) were not observed in the controls without OSD 4,7,15,27 .…”
Section: Resultsmentioning
confidence: 99%
“…Symptomatic athletes were included if they confirmed that maximum strength testing was possible. One athlete diagnosed with Osgood‐Schlatter disease was excluded from the analysis of pain, yet muscle and tendon data were included considering no evident reductions in training participation and the apparent lack of disease‐related changes of tendon mechanical properties 23 . The participants and their legal guardians gave written informed consent to the experimental procedures, which were approved by the ethics committee of the Humboldt‐Universität zu Berlin (vote from 16.02.2018) and carried out in accordance with the declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of real-time tissue elastography results of the rectus femoris muscles in 37 teenage male athletes, Enomoto et al rejected the hypothesis that one of the factors that lead to Osgood-Schlatter disease is higher-than-normal muscle stiffness. No significant difference in quadriceps muscle stiffness was found between the OGD and healthy groups [2].…”
Section: Osgood-schlatter Diseasementioning
confidence: 71%
“…Thus, a new, non-invasive, affordable, and objective test is urgently needed. We believe that elastography may prove to be such a tool in the future, as it has already been applied in hepatological, endocrinal, and oncological diagnostics [1,2]. Although far more studies on muscle elastography have been conducted in the adult population than in children, results from the former cannot be simply applied to the latter.…”
Section: Introductionmentioning
confidence: 99%